Building capacity for geo enabling health information systems supporting equitable health services and well being for all. - Ebener, Steeve (Metro Manila, Philippines Asian Development Bank, 2018)
Universal health coverage (UHC)equitable access to quality health services without undue financial hardship is the stated aim of almost every country in Asia and the Pacific. The effective management and use of geospatial data and technologies support efforts in achieving UHC. They also support the exchange and use of information by systems interoperability, especially in countries with weak registration systems. They enable countries to address health system inefficiencies and inequities, and as such improve health service delivery, planning, and management for better use of health sector resources to leave no one behind.
Keywords: Health; Information and communications technology; Electronic books